Effects of melatonin and N-acetylcysteine on lung ischemia reperfusion injury - Durkan, Atilla; Cakmak, Muharrem; Ulku, Refik; Ozekinci, Selver; Kale, Ebru (Bayrakol Medical Publisher, 2022)
Aim: In our study, we aimed to determine the effects of using melatonin, N-acetyl cysteine, and low potassium dextran solution (LPDS) as a preservative solution on ischemia/reperfusion injury. Material and Methods: A total of 48 male Sprague-Downey rats were used. Rats were divided into 8 groups: group 1: ischemia, group 2: ischemia+melatonin, group 3: ischemia + N-acetylcysteine, group 4: ischemia+melatonin + N-acetylcysteine, group 5: ischemia + reperfusion, group 6: ischemia + reperfusion + melatonin, group 7; ischemia + reperfusion + N-acetyl cysteine, and group 8; ischemia+reperfusion+melatonin+N-acetyl cysteine. Total antioxidant capacity (TAOC), malondialdehyde (MDA) and neutrophil values of each group were determined. The TAOC was obtained by spectrophotometric measurement of the absorption level of the color formed by the hydroxylion formed by the Fenton reaction with orthodianisidine. The MDA value was obtained spectrophotometrically using the thiobarbituric acid method, and the Neutrophil count was obtained as cell count using Papanicolau Stain stain. Results: While the highest TAOC values were in groups 4, 2, 3, 1, the lowest TAOC values were in groups 5,7,6,8. The highest MDA values were in groups 5, 7, 6, 1, 8, whereas the lowest MDA were in groups 4, 2, 3 (p<0.05). Neutrophil in bronchoalveolar lavage increased in groups 5,7,6,3,2,8,4. Discussion: In lung ischemia reperfusion, the use of melatonin and/or N-acetyl cysteine, and LPDS decreases plasma MDA levels and increases TAOC values. Additionally, the use of these antioxidants and preservation solutions decreases cell damage immunohistochemically, the cytokines mediating inflammation, the PMNL, and the inflammatory response associated with them.
Keywords: Ischemia; Melatonin; N-acetylcysteine; Reperfusion